Síntese e avaliação antimicrobiana de diésteres derivados cinâmicos - Dutra, Thalisson Firmo (2021)
Antimicrobial resistance is declared by the World Health Organization (WHO) as one of the top 10 threats to global public health, causing thousands of deaths each year. consequently, the search for new drugs is necessary among actions to combat antimicrobial resistance. Cinnamic derivatives stand out for their synthetic simplicity and wide potential for pharmacological activities, including antimicrobial activity. That way, the present work describes the synthesis of four series of diesters cinnamic derivatives, 2-alkyl-2-oxo-(E)-ethyl cinnamates, through the junction between potassium cinnamate salts with 2-chloroacetate esters, and in vitro antimicrobial assays were performed, evaluating the antibacterial, antifungal and antituberculosis activities. The diesters were obtained with yields between 71-98% and characterized by infrared (IR), nuclear magnetic resonance (NMR) hydrogen (1H) and carbon (13C) APT spectroscopic techniques. The minimum inhibitory concentration (MIC) values obtained from the tests were used to establish structure-activity relationships between the type of substituents in the aromatic ring (R: H, 3-NO2, 3,4-OMe and 3-F) and carbon chains alkyls (R': methyl, ethyl, propyl, isopropyl, butyl, sec-butyl and isobutyl) with inhibition activities against the tested microorganisms. Unsubstituted diesters exhibited ample antibacterial activity, with emphasis on Ethyl-2-ethoxy-2-oxo-(E)-cinnamate (1B) compound that had lowest MIC (32 μg mL-1) against Staphylococcus epidermidis ATCC-12288 and, antifungal activity, for compounds with small alkyl chains, against Aspergillus flavus strains LM-248 and ATCC-13013 (258 μg ml-1). Diesters with nitro and dimethoxy substituents were more selective for Proteus mirabilis ATCC-25933 (1024 μg mL-1), Trichophyton rubrum ATCC-28188 (128 μg mL-1) and Aspergillus flavus LM-248 (1024 μg mL-1) strains. Diesters with fluorine substituents exhibited ample antifungal activity with MIC = 1024 μg mL-1, but the increase in alkyl chain makes them inactive. The antituberculosis activity was little influenced by the substituents on the aromatic ring, but all active compounds against Mycobacterium tuberculosis H37Ra with MIC = 250-500 μM have alkyl chains of four carbon atoms.